Animals in Detective Fiction
XIII, 311 p. 1 illus. in color.
Keywords: This book explores the vast array of animals that populate detective fiction. If the genre begins, as is widely supposed, with Edgar Allan Poe’s “Murders in the Rue Morgue” (1841), then detective fiction’s very first culprit is an animal. Animals, moreover, consistently appear as victims, clues, and companions, while the abstract conception of animality is closely tied to the idea of criminality. Although it is often described as an essentially conservative form, detective fiction can unsettle the binary of human and animal to intersect with developing concerns in animal studies: animal agency, the ethical complexities of human/animal interaction, the politics and literary aesthetics of violence, and animal metaphor. Gathering its 14 essays into sections on ontologies, ethics, politics, and forms, Animals in Detective Fiction provides a compelling and nuanced analysis of the central role creatures play in this enduringlypopular and continually morphing literary form. Ruth Hawthorn is Senior Lecturer in American Literature at the University of Lincoln. She is currently completing a monograph on American detective fiction for the BAAS Paperbacks series with Edinburgh University Press. Her research interests include crime fiction, the literature of LA, and ecocriticism. John Miller is Senior Lecturer in Nineteenth-Century Literature at the University of Sheffield, President of ASLE-UKI (Association for the Study of Literature and the Environment, UK and Ireland), and co-editor of Palgrave Studies in Animals in Literature. His books include Empire and the Animal Body (Anthem, 2014) and The Heart of the Forest (British Library Publishing, 2022). .